The impact of interactivity features in enhancing online communication satisfaction - Mohd Azul Mohamad Salleh, (Universiti Kebangsaan Malaysian, 2012)
Online systems are providing more interactive forms of participation in workplaces and other kinds of organizations. The spread of Internet-based technologies has led to a rapid expansion of online systems and information management systems. This research seeks to examine the importance of interactivity features in enhancing users’ online communication satisfaction with Internet-based Information Management System (IBIMS) in four Malaysian research universities. This research uses the Outcome Interactivity Theory, communication satisfaction and Technology Acceptance Model (TAM) as the basis for constructing and measuring the relationship between interactivity features and online communication satisfaction. The data was gathered from 223 internal employees through a quantitative survey method. The results show that there is a significant relationship between interactivity features and online communication satisfaction when using IBIMS. This research makes a significant practical and theoretical contribution by integrating the interactivity features with technology acceptance to create users’ online communication satisfaction. Moreover, this research has created new knowledge on understanding users’ needs regarding online systems and applications at their workplace.